2002
DOI: 10.1002/mus.10189
|View full text |Cite
|
Sign up to set email alerts
|

Influences of electromechanical events in defining skeletal muscle properties

Abstract: Inactivity of the cat soleus muscle was induced via spinal cord isolation (SI), and the cats were maintained for 4 months. The soleus was electrically stimulated while lengthening (SI-L) or shortening (SI-S) during a simulated step cycle or during isometric (SI-I) contractions. For the SI, SI-S, SI-L, and SI-I groups, the soleus weights were 33, 55, 55, and 64% of the control, respectively, and the maximum tetanic tensions were 15, 30, 36, and 44% of the control, respectively. The specific tension was lower in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
39
0

Year Published

2002
2002
2016
2016

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 31 publications
(44 citation statements)
references
References 49 publications
5
39
0
Order By: Relevance
“…Even after brief periods of training, calcium dynamics in paralyzed muscle may begin to adapt [35]. These findings are consistent with animal studies, which have demonstrated that electrical stimulation (in concert with loading) prevents atrophy [45] and may prevent muscle fiber transformation [27,46]. Numerous studies have suggested that the dramatic training effects observed in electrically stimulated paralyzed muscle largely depend on the stimulation parameters used.…”
Section: Muscle Response To Trainingsupporting
confidence: 73%
“…Even after brief periods of training, calcium dynamics in paralyzed muscle may begin to adapt [35]. These findings are consistent with animal studies, which have demonstrated that electrical stimulation (in concert with loading) prevents atrophy [45] and may prevent muscle fiber transformation [27,46]. Numerous studies have suggested that the dramatic training effects observed in electrically stimulated paralyzed muscle largely depend on the stimulation parameters used.…”
Section: Muscle Response To Trainingsupporting
confidence: 73%
“…27 In addition, overexpression of FAK is associated with an increase in markers of an oxidative muscle phenotype. 9 There is a slow oxidative to fast glycolytic fiber type change following SCI, 19,28,29 and the loss of type 1 muscle fibers after SCI may be linked to or share common mechanisms with decreases in FAK expression and signaling. This agrees with previous data that shows cytomegalovirus-mediated FAK +FRNK overexpression into the rat soleus is associated with a decrease in type 1/2 muscle fiber hybrids and an increase in type 2 muscle fiber compared with overexpression with FAK alone.…”
Section: Discussionmentioning
confidence: 99%
“…It is also well documented that after SCI (in animals and humans), cauda equina injuries (in humans), and spinal isolation (in animals), reflex-generated exercise or direct electrical stimulation of muscle nerves induces recovery from myofiber atrophy in both primarily slow and primarily fast muscles and also opposes transformations in myofiber types toward faster isoforms (Dupont-Versteegden et al 1998;Hartkopp et al 2003;Kern et al 2004;Murphy et al 1999;Roy et al 1999Roy et al , 2002aShields and Dudley-Javoroski 2006). Thus the recovery of myofiber sizes and proportions in chronic spinal rats with long-term spasticity resembles the effects of training interventions that provide muscle activity after CNS lesions in animals and humans.…”
Section: Recovery Of Myofiber Types and Myofiber Morphology Resemblesmentioning
confidence: 99%
“…It is well documented that in the absence of muscle activity, myofibers often transform robustly toward faster, more fatigable types and undergo considerable atrophy (Roy et al 2002a). Early after spinal cord transection and after long-term spinal isolation in our rats, reduced muscle activity results in a similar atrophy and decrease in type I myofiber type proportions as seen in our results.…”
Section: Recovery Of Myofiber Types and Myofiber Morphology Resemblesmentioning
confidence: 99%
See 1 more Smart Citation